Dynamic Electroneurostimulation in Rehabilitation: a Prospective Randomized Study of 60 Patients after Surgical Treatment of Colorectal Malignancies - Victor A. Drobyshev; Lubov A. Shpagina; Andrey A. Vlasov; Marina V. Umnikova; Tatyana M. Smarzh (Вестник восстановительной медицины)
INTRODUCTION. Surgical treatment of colorectal malignancies, while increasing overall survival often determines the persistence ofthe pain syndrome, causing a decrease in the quality of life of patients. Pain-relieving medicines have side-effects and complications,which determines the search for and introduction of non-medicinal technologies. AIM. To evaluate the effectiveness of incorporating dynamic electroneurostimulation in the rehabilitation of patients after surgicaltreatment for colorectal cancer to correct pain syndrome, autonomic dysfunction and quality of life indices. MATERIAL AND METHODS. 60 male and female patients aged between 35 and 65 with a verified diagnosis of the colon and rectummalignant neoplasms after surgical treatment were examined in the conditions of the outpatient oncological care center at the StateMedical Institution “City Clinical Hospital No. 2” (Novosibirsk). They were divided into 2 groups: the 1st group (the main group, n=40)in addition to standard therapy received a 15-day course of dynamic electroneurostimulation (DENS) performed with «NEURODENSPCM» device, the 2nd group (the comparison group, n=32) received a standard treatment including chemotherapy, symptomaticpharmacotherapy and exercise therapy. The examination included assessment of pain syndrome using validated pain scales, thevegetative status, anxiety and depression, quality of life parameters. RESULTS AND DISCUSSION. The patients of the 1st group showed 1.2- and 2.4 times reduction of algias by the 5th and 15th day ofrehabilitation respectively. Upon completion of the rehabilitation the autonomic nervous system balance index (LF/HF) was adjustedby 4.8 and the centralization index by 6.0 times against the baseline, the anxiety and depression index on the HADS scale was reducedby 1.5 times, the quality of life on the SF-36 scale improved: physical functioning by 1.5 times, pain by 1.2 times, general health by 1.5times, which differed from the similar indicators in the 2nd group.Dynamic electroneurostimulation using NEURODENS-PCM device can have pain-relieving and vegetative-regulating effects due toactivation of antinociceptive brain structures and influence on suprasegmental parts of the autonomic nervous system. CONCLUSION. The inclusion of dynamic electroneurostimulation using «NEURODENS-PCM» device in the rehabilitation of patientsafter surgical treatment of malignant neoplasms in the colorectal region enables a faster relief of pain syndrome, adjustment of theneurovegetative regulation and the anxiety level, which contributes to improvement of the ' quality of life of patients.